2015
DOI: 10.1111/1440-1681.12479
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular resistance in response to iodinated contrast media in normal and functionally impaired kidneys

Abstract: SummaryContrast‐induced nephropathy (CIN) is considered to result from intrarenal vasoconstriction, and occurs more frequently in impaired than in normal kidneys. It was hypothesized that iodinated contrast media would markedly change renal blood flow and vascular resistance in functionally impaired kidneys. Thirty‐six patients were enrolled (32 men; mean age, 75.3 ± 7.6 years) undergoing diagnostic coronary angiography and were divided into two groups based on the presence of chronic kidney disease (CKD), def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…All these observations are line with the observed propensity towards increased RRI in subjects exhibiting CI-AKI. Last but not least, invasive measurement of intra-renal blood flow directly before and after CM administration revealed a significant increase of resistance index (defined as ratio of mean blood pressure and average peak renal velocity) and decrease of peak systolic velocity [7]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All these observations are line with the observed propensity towards increased RRI in subjects exhibiting CI-AKI. Last but not least, invasive measurement of intra-renal blood flow directly before and after CM administration revealed a significant increase of resistance index (defined as ratio of mean blood pressure and average peak renal velocity) and decrease of peak systolic velocity [7]. …”
Section: Discussionmentioning
confidence: 99%
“…During both pre- and post-procedural examination patients remained in supine position, as the majority of the patients were confined to this position following CA via femoral access. The ideal method should employ the measurement of resistive index by an invasive Doppler flow wire [7], which regrettably was not implemented in our study. Still, this technique may prolong the duration of the procedure and increase CM use and could trigger renal circulatory complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Recently, we reported that the Doppler flow wire method can be used to directly show the haemodynamics of the microvasculature of the kidney, and we demonstrated changes in microvascular haemodynamics following the administration of an iodinated contrast medium in a clinical setting. 6 However, changes in renal haemodynamics have not yet been fully validated in terms of the subclinical degree of kidney injury. All patients in the present study were scheduled for elective angiography without coronary intervention.…”
Section: To the Editormentioning
confidence: 99%